The Problem of Electrocution of Birds on Power Lines and the Progress of its Solution in the Middle Volga Basin - Sergey V. Bakka; Igor V. Karyakin; Nadezhda Y. Kiseleva (Пернатые хищники и их охрана)
Research aims to describe the progress in solving the “Birds and power lines (PL)” in Volga region. More than 80 scientific articles on the scale of bird mortality on PLs and ways to solve this problem, as well as more than 30 internet media publications served as the material for analysis.